Consórcio com leguminosa e/ou suplementação energética nos componentes não carcaça e na qualidade da carcaça e da carne de novilhos terminados em pastagem de aveia e azevém - Lisbinski, Eduardo (2015)
The objective of the experiment was to evaluate the effect of vetch and / or energy supplementation in winter pasture on the non-integral carcass components, the qualitative and quantitative characteristics of the carcasses of Nellore cattle. The study occurred in the Paraná Federal Technological University Campus Dois Vizinhos, from June to November 2013. It was used 18 steers with an average age of 23 months and 430 kg of live weight, kept in three treatments (oat + ryegrass + vetch, oats + ryegrass + vetch + supplements; oat + ryegrass + supplement) in a period of 100 days with herbage allowance of 10% of body weight. The average forge mss was around 1700kg DM ha-1. After the end of the grazing period, the animals were slaughtered in a commercial slaughterhouse, respecting the legislations and with a human slaughter. All non-housing integral components were separated and weighed, it was related to 100 kg of empty body weight. Morphometric measurements in the carcass and meat sensory evaluation were performed. The data were evaluated by analysis of variance and Tukey’sposthoc test with statistical significance deemed at 10%. Also in the study was realized the correlation between the dependent variables by calculated by means of the Pearson correlation coefficient and contrast test. The different feeding systems did not affect in the empty body weight, non-housing integral components, set of vital organs and set of external bodies. For the internal organs, only the relative liver weight was increased in the treatment oats + rye grass + vetch (P <0.05). rye grass + vetch + supplement showed higher values in the relative weights of the deposited fat in TGI and total fat. Animals that remained in treatment consists of oats + rye grass + vetch + supplement showed (P <0.05) higher slaughter weights. The cold carcass yields did not suffer influence of treatments. The conformation of the carcasses was higher in the treatment oats +rye grass + supplement. The morphometric measurements were not affected by treatments. The treatment oats + rye grass + vetch + supplement showed (P <0.10) more clearly meat mad more palatability. The treatment consisted by oats + rye grass + vetch + supplement was superior to the others, with the highest weight slaughter, greater amount of front part and better quality characteristics of the meat.